2018
DOI: 10.1111/liv.13957
|View full text |Cite
|
Sign up to set email alerts
|

P57‐mediated autophagy promotes the efficacy of EGFR inhibitors in hepatocellular carcinoma

Abstract: Through activating the PI3K/AKT/mTOR signalling pathway, p57 can reverse Er/C-225-induced autophagy, and thereby increase the therapeutic efficiency of Er/C-225 treatment. Given these results, p57 up-regulation may be applicable as a therapeutic strategy to improve EGFR-targeted therapy in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…36 Specifically, an enhancement in the extent of PI3K, Akt, and mTOR phosphorylation was reported to be involved in the decline of LC3B-II in HCC. 37 However, in this study, the potential association between LINC01419 and the PI3K/Akt/mTOR signaling pathway requires further exploration, verifying specific molecular targets verified by more experiments, such as RNA immunoprecipitation (RIP), cross-linking immunoprecipitation (CLIP), chromatin immunoprecipitation (CHIP), and fluorescence in situ hybridization (FISH).…”
Section: R E T R a C T E Dmentioning
confidence: 87%
“…36 Specifically, an enhancement in the extent of PI3K, Akt, and mTOR phosphorylation was reported to be involved in the decline of LC3B-II in HCC. 37 However, in this study, the potential association between LINC01419 and the PI3K/Akt/mTOR signaling pathway requires further exploration, verifying specific molecular targets verified by more experiments, such as RNA immunoprecipitation (RIP), cross-linking immunoprecipitation (CLIP), chromatin immunoprecipitation (CHIP), and fluorescence in situ hybridization (FISH).…”
Section: R E T R a C T E Dmentioning
confidence: 87%
“…EGFR is an important factor in HCC and previous studies have demonstrated that EGFR is involved in various HCC mechanisms including cell proliferation, latestage metastasis, treatment and drug resistance. [30][31][32][33][34][35] However, anti-EGFR agencies do not show ideal results in HCC involving extremely complicated pathways. 10,12 Lin et al reported that the anti-EGFR drug resistance in HCC is caused by the promoted interaction of EGFR with mTORC2.…”
Section: Discussionmentioning
confidence: 99%
“…The P57-mediated autophagy promotes the efficacy of EGFR [epidermal growth factor receptor] inhibitors. Upregulation of p57 decreases the level of autophagy and enhances the decrease in cell viability in hepatocellular carcinoma [40]. In addition, p57 expression makes cancer cells more sensitive to cisplatin.…”
Section: Cis-cet Me L-cis-cetmentioning
confidence: 99%